CBT HOTS Assessment Instrument Model: Teacher Perception Analysis of a Role of Illustration as Well as Quiz and Question Setting According to HOTS - Yuni Evi Meliani Sihaloho; Undang Rosidin; Agus Suyatna (Jurnal Pembelajaran Fisika, 2020)
21st Century Learning requires HOTS learning to improve students' higher-order thinking skills, in addition to learning that promotes HOTS assessment must also promote HOTS. However, there are still many teachers who have not done HOTS who are able to stimulate students' high-level thinking skills well. This study discusses teacher perceptions about HOTS CBT assessment instrument models about the role of illustrations and quizzes and questions set in measuring HOTS. This type of research is a mixed method. The mixed-method strategy used is Sequential Explanatory Strategy. This research was conducted on five high school physics teachers in Metro City. Data collection using teacher perception respondents questionnaire conducted in April 2019 by five high school physics teachers in Metro City. The data collected was analyzed descriptively quantitatively. As many as 96% of teachers strongly agree that the Computer Based Test Model (CBT) involves video illustrations, animations, simulation questions, 80% of teachers agree that describing items can enrich thinking levels (C1, C2, C3, C4, C5, C6) and GPA for considered, as well as 96% of teachers strongly agree with the form of illustration of video items, animations, complications can be removed verbalism. In addition to questions and types of questions, quizzes and question settings are considered necessary by teachers to improve higher-order thinking skills (HOTS). Based on the data obtained the validation instrument was developed to obtain the best types of questions, stimuli, as well as quizzes and question settings in improving students' higher-order thinking skills (HOTS).Keywords: HOTS CBT assessment, stimulation, 3 types of questions, quizzes and question settingsDOI: http://dx.doi.org/10.23960/jpf.v8.n1.202002